Analisis Pengaruh Pengembangan Kurikulum Pendidikan Vokasi Yang Relevan Dengan Dunia Kerja - Callista Tantia Rustandi; Novita Elfalina Zahara; Ichsan Fauzi Rachman (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
The development of vocational education curricula relevant to the needs of the labor market is essential in enhancing graduates’ readiness to face the increasingly dynamic job market. This study aims to analyze the impact of vocational education curriculum development that aligns with industrial needs. Using the literature study method, this research identifies the key factors influencing curriculum relevance, evaluates the extent to which the current curriculum meets labor market expectations, and examines the impact of curriculum changes on graduates’ employability skills. The results show that developing an industry-based curriculum and employing teaching methods such as Lesson Study and Project-Based Learning (PBL) can enhance the effectiveness of vocational education. Collaboration with the industrial sector, including curriculum design, provision of practical facilities, and teacher training, plays a significant role in preparing skilled and job-ready graduates. Moreover, curriculum adaptation to technological advancements and labor market changes is crucial to maintaining the relevance of graduate competencies. These findings make a significant contribution to formulating vocational education policies in Indonesia to become more responsive to global challenges. They also provide strategic recommendations to enhance graduates’ employability through adaptive and industry-based curricula. Keywords: Industrial Sector, Employability, Lesson Study, Vocational Education, Curriculum Development, Project-Based Learning